Accounting for Equity Financial Instruments under International Financial Reporting Standard (IFRS) 9 Financial Instruments: Use, Determinants, Usefulness, and Cost - Zang, Zeting (Auckland University of Technology, 2025)
Standard setters, professional bodies, and practitioners consistently identify accounting for financial instruments as one of the standards that raises the most onerous concerns. Since the global financial crisis, there has been a growing demand to improve and simplify financial instruments reporting. The International Financial Reporting Standard (IFRS) 9 Financial Instruments replaced the International Accounting Standard (IAS) 39 Financial Instruments: Recognition and Measurement, with an effective date of on or after 1st January 2018. Some of the reporting complexities come from accounting for equity financial instruments (EFAs), which present an important portion of companies’ total assets. The prohibition of recycling fair value gains or losses on EFAs upon their derecognition and mandating fair value measurement without cost option are some of the major changes for EFA accounting in IFRS 9. Given the standard changes, this thesis investigates the use of EFAs, determinants of EFA classification, the value relevance of EFA information, costs related to EFAs, and whether these have been changed post IFRS 9. The investigation is conducted in three empirical studies in the context of EFA accounting standard changes under IFRS 9 in Australian listed companies. The first study of this thesis examines the use of EFAs and their classification choice before and after IFRS 9. Using a sample of Australian Securities Exchange (ASX) 300 firms one year before and after IFRS 9 adoption, I find a significant increase in the classification of EFAs at fair value through profit or loss (FVTPL) post IFRS 9 via improved disclosure clarity regarding the classification choice. However, fair value through other comprehensive income (FVTOCI) remains the most widely used classification choice for EFAs both before and after IFRS 9. Although some evidenceshows that EFA classification location has a significant impact on financial firms’ profitability ratios, the majority of firms have limited effect on profitability from their choice of EFA classification. The first study also provides descriptive evidence of the variations in the use of EFAs and classification behaviour between sectors and firm sizes. Using a sample of both financial and non-financial ASX firms three years before and after IFRS 9 adoption, the second study examines factors that affect the choice of EFA classification and the usefulness of EFA information. I find that there is no practical change in the use of EFAs after IFRS 9 in both financial and non-financial firms, regarding whether to invest in EFAs or not, classification choice, and holding amounts. This result is in line with some evidence in Europe but in contrast to China. EFA classification determinants analysis implies a potential opportunistic use of the discretion given in IAS 39 to consider EFA effect on net income and contractual incentives of risk and compensation when making the classification decision in non-financial firms. Prior to IFRS 9, the opportunistic use of the EFA classification choice is also found in financial firms when they are exposed to a higher contractual risk. However, the potential exploitation of the accounting choice is constrained after IFRS 9. EFA amounts provide value relevance when they comprise a large portion of total assets after IFRS 9. The EFA effect on OCI only provides incremental value relevance in financial firms before but not after IFRS 9. The third study of this thesis examines whether EFAs are related to audit fees and whether the relationship changed post IFRS 9 in non-financial ASX companies. I find that EFA holding is significantly positively related to audit fees, and this is driven by large companies. I further examine which EFA attributes drive the relationship and find that the higher audit fees are related to EFAs that are measured at level 3 fair value hierarchy, notEFA amounts or the classification location. There is no evidence that the relationship between audit fees and EFA holding or EFA attributes changed post IFRS 9. In addition, I find that audit efficiency is not affected by EFAs, regardless of IFRS 9 adoption. Overall, the contributions of this thesis are twofold. Firstly, the results of this thesis contribute to the standard-setting debates, which centre on whether to allow the FVTOCI option for EFA classification and recycle fair value gains or losses on EFAs from equity to profit or loss. The results provide insight to standard setters and regulators for future revision. Secondly, this thesis extends the literature on IFRS 9 by examining the effect and consequences of standard changes for EFAs, specifically. The results shed some light on the use of EFAs and the potential benefits and costs of IFRS 9.